ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI BRAND LOYALTY MELALUI BRAND TRUST PADA PENGGUNA BRAND LOKAL - Efriza Shahara Kennedi; Lady Lady (Media Bina Ilmiah, 2023)
This research was conducted with the aim of proving brand experience, perceived value, brand personality, brand image, product quality and service quality on brand loyalty with brand trust as a mediating variable on local brand users. The population in this research is the people of Batam who use local brand users. Purposive sampling method was used to collect samples by taking samples based on certain considerations, namely that respondents were using local brand users. The questions in this study were 22, so the smallest number of samples required was 22 x 10 = 220 samples. To ensure the data is met and there are no shortages, the questionnaire will be distributed to 250 respondents. The data was processed using the Smart Partial Least Square (PLS) 3.0 program. The results of this study indicate that the independent variable on the brand trust mediation variable is 0.553, which means that the independent variable can explain the mediating variable as much as 55.3% while 44.7% is explained by other variables. The independent variable can explain the dependent variable as much as 80.3%. While 19.7% is explained by other variables. The results of the quality index are declared large because the GOF value is greater than 0.36